2011
DOI: 10.1161/hypertensionaha.110.158915
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Overexpression Exacerbates Pressure Overload–Induced Cardiac Remodeling Through Enhanced Inflammatory Response

Abstract: Abstract-Serum C-reactive protein (CRP) elevation predicts the development of heart failure in patients with hypertension. CRP activates macrophages and enhances oxidative stress. We hypothesize that CRP itself has a pathogenic role in the development of pressure overload-induced cardiac remodeling. Transgenic mice with human CRP overexpression (CRPtg) and nontransgenic littermates (CON) were subjected to transverse aortic constriction (TAC/CRPtg and TAC/CON) or sham operation (Sham/CRPtg and Sham/CON). One we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 37 publications
3
42
0
Order By: Relevance
“…Recently, the study has demonstrated that a low‐grade inflammatory response may play a significant role in the phenotypic expression of myocardial fibrosis in HCM 17. Previous studies found that CRP may have a pathogenic role in the development of cardiac hypertrophy and fibrosis, possibly through the nuclear factor kappa B signaling pathways 24. Zhang et al also found that activation of the nuclear factor kappa B signaling pathways may be the mechanisms by which CRP promotes cardiac fibrosis 25.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the study has demonstrated that a low‐grade inflammatory response may play a significant role in the phenotypic expression of myocardial fibrosis in HCM 17. Previous studies found that CRP may have a pathogenic role in the development of cardiac hypertrophy and fibrosis, possibly through the nuclear factor kappa B signaling pathways 24. Zhang et al also found that activation of the nuclear factor kappa B signaling pathways may be the mechanisms by which CRP promotes cardiac fibrosis 25.…”
Section: Discussionmentioning
confidence: 99%
“…Nagai et al 26 showed that transgenic transverse aortic constriction mice overexpressing the human CRP gene had higher myocardial messenger RNA levels of interleukin-6, CD68 and collagen-I, and greater levels of infiltrating Mac-2-positive macrophages and reactive oxygen species than nontransgenic  transverse aortic constriction mice. At 4 weeks after surgery, the heart and lung weights and extent of cardiac fibrosis were greater in transgenic transverse aortic constriction mice.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that CRP itself may play some role in the development of LV dysfunction and remodeling [9].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 93%
“…Increased level of CRP is associated with left ventricular (LV) dysfunction and demonstrate higher mortality and morbidity risk in patients with heart failure. It is an independent factor of ischemic or non-ischemic etiology and other cardiovascular risk factors [9]. CRP is reported to promote fibrosis and inflammation in angiotensin II induced myocardial remodeling [10].…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%